Garlic, cold storage and heating effects in controlling Escherichia Coli O157:H7 in ground beef - Ceylan, E.; Hunt, Melvin C.; Fung, Daniel Y. C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This research evaluated the effect of garlic, cold storage and heating on Escherichia coli O157:H7 in ground beef patties. Ground beef (20% fat) inoculated with E. coli O157:H7 to an initial inoculum level of 8 log10 CFU/g, was mixed with 0.5, 1.0 and 1.5% garlic powder (wt/wt). Samples were stuffed into 1 inch diameter test tubes and incubated at 40°F for 24 hr. Tubes were heated to internal temperatures of 125, 130, 135, 140, 145, 155 and 160°F, and E. coli O157:H7 was enumerated. Garlic addition lowered E. coli O157:H7 survival in ground beef heated to 150 and 155°F, and no organisms were found in beef heated to 160°F. This slight effect may enhance safety of ground beef, but is not a substitute for cooking ground beef to 160°F.
Keywords: Beef; Ground beef; E. coli O157:H7; Garlic; Cooked temperature